English Learning and Teaching are Like a Rollercoaster: Metaphor of Online Learning amid COVID-19 Outbreak in Indonesia - Rafika Rabba Farah; Nur Mafissamawati Sholikhah (Makassar State University, 2021)
Abstract. The global pandemic of COVID-19 has a direct impact on educational setting, schools and universities finally have to use an online platform as a way out. This present research aims to analyse EFL students’ and teachers’ perception on their online learning during the outbreak using metaphoric words. A questionnaire using metaphor analysis concept was distributed online to 55 students and 14 teachers at one private university in Indonesia. Data coding was done through qualitative analysis software, NVivo 12 Plus. Results show that EFL students and teachers have various metaphoric entailments to describe their perceptions. Three major metaphoric words used by students were related to hobby, game, and food for 11 coding references respectively, whereas for teachers the metaphoric used were hobby (4 coding references); game (3 coding references); relationship (2 coding references), others was in small distribution. Derived from the metaphoric words used by the students and teachers, the nuance can be drawn into their perspectives towards the online learning. The results also revealed that EFL students perceived online learning negatively; whereas, teachers were mostly in a neutral position towards their online teaching. This study has shed a light that this pandemic has essentially shown that in the future educational curriculum, particularly in EFL context, online learning activities should be made a part of ELT class.Keywords : COVID-19, Online Learning, EFL Learners, Metaphor Analysis